Mod 6

Four positive integers a a , b b , c c , and d d are such that

{ ( a + b + c + d ) m o d 6 = 1 ( a + b + c ) m o d 6 = 0 ( a + b ) m o d 6 = 0 a m o d 6 = 3 \large \begin{cases} \begin{aligned} (a+b+c+d) \bmod 6 & = 1 \\ (a+b+c) \bmod 6 & = 0 \\ (a+b) \bmod 6 & = 0 \\ a \bmod 6 & = 3 \end{aligned} \end{cases}

What is ( 2 ( a d ) + c 2 3 b ) m o d 6 \big(2(a-d)+c^2-3b\big) \bmod 6 ?


Try this


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jordan Cahn
Dec 21, 2018

Using the given clues, from the bottom up, we see that

  • a 3 m o d 6 a\equiv 3\bmod 6
  • b 3 m o d 6 b\equiv 3\bmod 6
  • c 0 m o d 6 c\equiv 0\bmod 6
  • d 1 m o d 6 d\equiv 1\bmod 6

Thus 2 ( a d ) + c 2 3 b 2 ( 3 1 ) + 0 2 3 ( 3 ) 4 9 1 m o d 6 2(a-d) + c^2 -3b \equiv 2(3-1) + 0^2 -3(3) \equiv 4 - 9 \equiv 1 \mod 6

Chew-Seong Cheong
Dec 21, 2018

a 3 (mod 6) Given a + b 3 + b 0 (mod 6) b 3 (mod 6) a + b + c 0 + c 0 (mod 6) c 0 (mod 6) a + b + c + d 0 + d 1 (mod 6) d 1 (mod 6) \begin{aligned} a & \equiv 3 \text{ (mod 6)} & \small \color{#3D99F6} \text{Given} \\ a+b & \equiv 3 + b \equiv 0 \text{ (mod 6)} & \small \color{#3D99F6} \implies b \equiv 3 \text{ (mod 6)} \\ a+b+c & \equiv 0 + c \equiv 0 \text{ (mod 6)} & \small \color{#3D99F6} \implies c \equiv 0 \text{ (mod 6)} \\ a+b+c + d & \equiv 0 + d \equiv 1 \text{ (mod 6)} & \small \color{#3D99F6} \implies d \equiv 1 \text{ (mod 6)} \end{aligned}

Therefore, 2 ( a d ) + c 2 3 2 ( 3 1 ) + 0 2 3 1 (mod 6) 2(a-d) + c^2 - 3 \equiv 2(3-1)+0^2 - 3 \equiv \boxed 1 \text{ (mod 6)} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...